1994
DOI: 10.1007/bf02257796
|View full text |Cite|
|
Sign up to set email alerts
|

Colorectal cancers of rare histologic types compared with adenocarcinomas

Abstract: Colorectal cancers of histologic varieties other than adenocarcinoma have distinctive epidemiologic and clinical traits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0
6

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 15 publications
5
25
0
6
Order By: Relevance
“…19 However, a study using data from the Utah cancer registry found a greater proportion of squamous cell cancers (listed as a subtype of epidermoid cancers in this study) in females. 20 That study also found more colonic carcinoid tumors in females, in agreement with our carcinoid findings. 20 A Dutch population-based study also revealed a significant female predominance for carcinoid tumors in individuals under the age of 50.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…19 However, a study using data from the Utah cancer registry found a greater proportion of squamous cell cancers (listed as a subtype of epidermoid cancers in this study) in females. 20 That study also found more colonic carcinoid tumors in females, in agreement with our carcinoid findings. 20 A Dutch population-based study also revealed a significant female predominance for carcinoid tumors in individuals under the age of 50.…”
Section: Discussionsupporting
confidence: 91%
“…20 That study also found more colonic carcinoid tumors in females, in agreement with our carcinoid findings. 20 A Dutch population-based study also revealed a significant female predominance for carcinoid tumors in individuals under the age of 50. 21 With regard to mucin-producing tumors, a study with surveillance data covering 10%-14% of the U.S. population also found higher proportions of these tumors among females 22 ; however, a Singapore cancer registry study concluded that the frequency of mucin-producing tumors was similar for both sexes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Whilst relief from intestinal angina may be immediate, little response would be expected from the pain of intestinal obstruction. At an advanced stage, intestinal ischaemia may cause necrosis and perforation of the intestinal wall, also a recognised cause of death in patients with midgut carcinoid (Eckhauser et al 1981 Thompson et al 1985, Moertel et al 1987, Norheim et al 1987, Saha et al 1989, Makridis et al 1990, Ballantyne et al 1992, Soreide et al 1992, Levi et al 1993, 2000, DiSario et al 1994, McDermott et al 1994, Norton 1994, Ahlman 1996, Stinner et al 1996, Wä ngberg et al 1996, Burke et al 1997, Cunningham et al 1997, Modlin & Sandor, 1997, Soga 1997, 1998a,b, Sandor & Modlin 1998, Shebani et al 1999, Onaitis et al 2000, Quaedvlieg et al 2001, McCusker et al 2002, Talamonti et al 2002, Modlin et al 2003. 2 Approximate percentage survivals in selected patients from collected publications (Bechstein & Neuhaus 1994, Lang et al 1997, Le Treut et al 1997, Chen et al 1998, Lehnert, 1998, Chamberlain et al 2000, Yao et al 2001).…”
Section: Mesenteric Metastases Natural Historymentioning
confidence: 99%
“…Pure squamous cell carcinoma (SCC) is a histologic subtype of tumors of epithelial origin that is not uncommon in glandular organs such as lung and pancreas, but accounts for only 0.1 to 0.25 cases per 1,000 colorectal carcinomas [2][3][4][5]. After the first case report in 1919 [6], a total of 74 pure SCC of the colorectum and 147 of mixed squamous and adenosquamous cancer cases have been reported in the literature [5,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%